Penerapan Prinsip Rule of Six dalam Pascaproduksi Reels Instagram oleh Tenchi Tirtayasa - Nazwa Rivie Azahra; Abung Supama Wijaya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the application of Walter Murch's Rule of Six as a post-production decision-making framework for the Instagram Reels content on the Tenchi Tirtayasa account. This project addresses the challenge of bridging the gap between the image of a premium restaurant and the necessity to convey a warmer, more accessible brand experience through short-form videos. A descriptive project-based methodology was employed, involving the observation of the production process, documentation of the editing workflow, analysis of Episode 3 of the Reels series, and review of Instagram Reels Insights as the data. The analysis reveals that the six priorities of editing—Emotion, Story, Rhythm, eye-trace, Two-dimensional screen space, and Three-dimensional action space—assisted the editor in selecting shots, organizing visual sequences, managing pacing, and maintaining spatial continuity in the vertical 9:16 format. Episode 3 garnered 9,132 Views, 229 Likes, 10 Comments, 9 Shares, and a 93.4% non-follower reach rate. These findings suggest that a Rule of Six-based workflow can enhance soft-selling Storytelling, reinforce visual consistency, and improve the communicative value of restaurant reel content.